Effect of alterations of dietary sodium on the severity of asthma in men. Issue 7 (July 1993) - Carey, O J; Locke, C; Cookson, J B
Abstract : BACKGROUND--There is some evidence of a positive association between increased dietary salt consumption and both increased bronchial reactivity and mortality from asthma in men. This study assesses the effects of alterations in dietary salt consumption on the clinical severity of asthma in adult male asthmatic patients. METHODS--A randomised, double blind, placebo controlled, crossover design was employed. Twenty seven mild to moderate asthmatic patients were established on a low sodium diet (80 mmol/day) at the end of a 4-5 day run in period and then randomised to receive 200 mmol/day slow sodium or matching placebo for five weeks, crossing over to the alternative regime for a further five weeks. Patients used diary cards to record twice daily peak expiratory flow rates, daily symptom scores, and bronchodilator consumption. Spirometry and degree of bronchial responsiveness (methacholine challenge test) were measured at screening and at the end of each treatment period. Twenty four hour urinary sodium excretion was measured at screening and in duplicate for each treatment period. RESULTS--Twenty two patients completed the study. For these patients the mean (95% confidence interval (CI)) difference in 24 hour sodium excretion between treatments was 204 (175 to 235) mmol. Compared with placebo, sodium supplementation resulted in deleterious alterations of all measured parameters. Bronchial reactivity rose on slow sodium with a 0.73 (0.2 to 1.3) doubling dose methacholine difference compared with placebo. Estimated median (95% CI) difference in bronchodilator consumption was 1.3 (0.4 to 2.1) puffs per day, the estimated median difference in symptom score was 0.6 (0.2 to 0.9), and mean forced expiratory volume in one second fell by 0.21 (0.05 to 0.37) 1. The peak expiratory flow rate rose on placebo and fell on slow sodium. Median differences between treatments were 5.6% (2.2% to 9.8%) for morning and 7.8% (3.9% to 12.9%) for evening peak expiratory flow rate. CONCLUSIONS--Our results suggest that large increases in dietary sodium result in physiological deterioration and increased morbidity in male asthmatic patients.